FACTORS ASSOCIATED WITH DURATION OF EXCLUSIVE AND TOTAL BREASTFEEDING IN MUNICIPAL DAYCARE CENTERS IN JUIZ DE FORA-MG, BRAZIL - Thais Campos Martins; Ana Paula Carlos Cândido; Daniela da Silva Rocha; Renata Maria Souza Oliveira; José Otávio do Amaral Corrêa; Michele Pereira Netto (Universidade do Estado do Rio de Janeiro, 2019)
Objective: To identify factors associated with the duration of exclusive and total breastfeeding in children from the municipality of Juiz de Fora, Minas Gerais. Methodology: Cross-sectional study, with a sample of 548 and 416 children for the outcomes of duration of exclusive and total breastfeeding, respectively, performed with children under five years old enrolled in municipal daycare centers. Data on socioeconomic conditions, mother and children characteristics, and information about breastfeeding and introduction of complementary feeding were collected in interviews with the parents. Statistical analysis was performed through univariate linear regression, electing variables with p<0.20. Next, hierarchical multiple linear regression was developed, and final models were generated for the studied outcomes. Results: Only 6.2% of the children were exclusively breastfed until the sixth month and 16.1% were breastfed along with complementary feeding until two years of age. In the hierarchical analysis, the variables that showed association with the duration of exclusive breastfeeding were "cesarean section" (β= -12.35; p= 0.017) and "birth length" (β= 1.52; p= 0.022). For the duration of total breastfeeding, the variables "duration of exclusive breastfeeding" and "age of introduction of thickeners" were associated with the outcome (β=1,23, p=0,012; β=0,56; p=0,000, respectively). Conclusion: The factors associated with longer duration of exclusive and total breastfeeding were: natural birth, longer birth length, longer duration of exclusive breastfeeding, and late introduction of thickeners in the child's food. These data show the importance of focusing on mother and child health, since prenatal care until the introduction of complementary feeding. DOI: 10.12957/demetra.2019.43583